2016
DOI: 10.1080/14763141.2016.1182580
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different foot and hand set-up positions on backstroke start performance

Abstract: Foot and hand set-up position effects were analysed on backstroke start performance. Ten swimmers randomly completed 27 starts grouped in trials (n = 3) of each variation, changing foot (totally immersed, partially and totally emerged) and hand (lowest, highest horizontal and vertical) positioning. Fifteen cameras recorded kinematics, and four force plates collected hands and feet kinetics. Standardised mean difference and 95% confidence intervals were used. Variations with feet immersed have shown lower verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…Since contact time was not significantly different between conditions, this difference in impulse is likely due to a change in the magnitude of the applied forces. These findings are comparable to previous research which compared above and below water foot positioning; starts with the feet placed above the water had a greater horizontal impulse and takeoff velocity but no significant difference in time to 10 m [24]. These seemingly contradicting data highlight the importance of considering all phases of the start, and not simply the block phase.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Since contact time was not significantly different between conditions, this difference in impulse is likely due to a change in the magnitude of the applied forces. These findings are comparable to previous research which compared above and below water foot positioning; starts with the feet placed above the water had a greater horizontal impulse and takeoff velocity but no significant difference in time to 10 m [24]. These seemingly contradicting data highlight the importance of considering all phases of the start, and not simply the block phase.…”
Section: Discussionsupporting
confidence: 82%
“…In existing backstroke start literature, different methods and analysis techniques make direct comparison between studies difficult [13]. Furthermore, most studies which discuss different start configurations [18,[23][24][25] were performed prior to recent equipment changes, and thus their findings may no longer be relevant. The few studies which discuss different configurations while using the backstroke ledge only manipulate hand position [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…23 QTM version 2.8 software was used to track and process the anatomical markers on the swimmers' bodies using a fit-to-seconddegree curve filter. 25 Swim velocity, stroke length, phase time, stroke rate, and knee angle for the complete stroke cycle and for each of the phases were measured. Based on the leg kick, each stroke cycle was divided into 3 phases: leg propulsion, from the smallest knee angle during leg recovery until the first peak in knee angle (extension) during the leg propulsion; leg glide, from end of leg propulsion to the beginning of active knee flexion for leg recovery; and leg recovery, from end of leg glide until the smallest knee angle.…”
Section: Data Processingmentioning
confidence: 99%
“…Third, we chose to examine the wall-contact phase of the start in this study because previous research suggests the plyometric warm-up only affects the explosive "push-off" portion of the start [8,9]. However, we acknowledge that body position during flight and water entry also affects performance [16,21,37]. Fourth, we collected EMG only on the right side, and tracked joint position only on the left side of participants.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, we did not collect foot and hand forces. Previous research evaluating swimming dive starts [10], relay takeovers [38] and backstroke starts [4,21,37] have shown that changes in start kinetics are often not connected to changes in start time. Accordingly, time to 10 m appears to be more sensitive than kinetics as a measure of swim start performance based on the larger effect size.…”
Section: Limitationsmentioning
confidence: 99%